Profesi Akuntan Syariah Indonesia Memasuki Masyarakat Ekonomi Asean (MEA) - Agus Arwani (IAIN Salatiga, 2016)
Accountants are the actors who contribute to the establishment andimplementation of accounting as a structure. On the other hand theconsequences of the application of modern accounting shows the impact ofa less than satisfactory. Facts show the number of accounting manipulationscandal that hit the company’s financial statements and the low awarenessof their social responsibility and the environment implies that very largechanges in accounting principals. Accounting reality is part of how accountants take on the role. Deviations reality always brings accountants as party central is how actors and structures form mutually met. Habitus actor ‘’ greedy ‘’ met with accounting (capitalism) as a structure that legitimize it. In reality accountant (agent) looks so lost in the shackles of capitalism, so the agency theory in the form of a conflict of interest, it seems to shift the basis of mutual symbiosis between the interests of management and accountants. Accountants must be returned khittah her as a sovereign profession, he is an ideologue as Rausyan Fikr. All forms of deep-an accountant in worship, glorify the ‘’ number ‘’ in the sense of making all tasks as tasks (treatises) ‘’ prophetic ‘’ to map the right stakeholders fairly and correctly. This can only take place within the awareness frame of the Godhead (fervently) to put God at the summit toward accountability. Readiness accountant sharia in entering the MEA in 2016 with preparing the capabilities and expertise of sharia-based accounting standards IFRS, Accounting Sharia must understand the risks of sharia, sharia accountingshould be standardized SDI International, science and technology capabilitiesaccountant sharia be reliable